Modelo experimental de úlcera traumática em mucosa jugal de ratos - Cavalcante, Galyléia Meneses; de Paula, Renata Janaína Sousa; de Souza, Leonardo Peres [UNESP]; Sousa, Fabrício Bitu; Mota, Mário Rogério Lima; Alves, Ana Paula Negreiros Nunes (FapUNIFESP (SciELO), 2011)
Purpose: To establish an experimental model of traumatic ulcer in rat cheek mucosa for utilization in future alternative therapy studies. Methods: A total of 60 adult male rats (250 - 300g) were used. Ulceration of the left cheek mucosa was provoked by abrasion using a n o 15 scalpel blade. The animals were observed for 10 days, during which they were weighed and their ulcers were measured. The histological characteristics were analyzed and scored according to the ulcer phase. In the statistical analysis, a value of p<0.01 was considered a statistically significant response in all cases. Results: During the five first days, the animals lost weight (Student t test, p<0.01). The ulcerated area receded linearly over time and was almost completely cicatrized after 10 days (ANOVA, Tendency post-test, p<0.0001). Groups on days 1, 2 and 3 days displayed similar results, but a decrease in scores were observed after the 4th day. Conclusion: The proposed cheek mucosa ulcer model in rats can be considered an efficient, low-cost, reliable, and reproducible method.
Experimental model of traumatic ulcer in the cheek mucosa of rats
Keywords: Mouth mucosa; Rats; Ulcer; Wound heling; abrasion; analysis of variance; animal experiment; animal model; animal tissue; body weight; cheek mucosa; cost; disease course; histology; male; mouth ulcer; nonhuman; rat; reliability; reproducibility; scalpel; scoring system; weight reduction; Animals; Cheek; Disease Models, Animal; Male; Mouth Mucosa; Oral Ulcer; Time Factors; Wound Healing